2009
DOI: 10.1111/j.1530-0277.2009.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Circadian Clock Exhibits Acute Tolerance to Ethanol

Abstract: Background-Tolerance to ethanol is observed over a variety of time courses, from minutes to days. Acute tolerance, which develops over 5-60 minutes, has been observed for both behavioral and neurophysiological variables, and may involve changes in signaling through NMDA, GABA, or other receptors. Previous work has shown that both acute and chronic ethanol treatments modulate photic and non-photic phase resetting of the mammalian circadian clock located in the suprachiasmatic nucleus (SCN). Although not specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
1
29
2
Order By: Relevance
“…Although we did not measure Clock expression in the SCN, others have shown that the SCN is responsive to ethanol (Chen et al, 2004;Prosser and Glass, 2009;. Studies in different species have illustrated that circadian clock neurons are important for alcohol tolerance and that alcohol can modulate circadian phase-shifting (Brager et al, 2010;Ghezzi et al, 2013;McElroy et al, 2009;Prosser and Glass, 2009;Ruby et al, 2009;.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although we did not measure Clock expression in the SCN, others have shown that the SCN is responsive to ethanol (Chen et al, 2004;Prosser and Glass, 2009;. Studies in different species have illustrated that circadian clock neurons are important for alcohol tolerance and that alcohol can modulate circadian phase-shifting (Brager et al, 2010;Ghezzi et al, 2013;McElroy et al, 2009;Prosser and Glass, 2009;Ruby et al, 2009;.…”
Section: Discussionmentioning
confidence: 89%
“…Although we did not measure Clock expression in the SCN, others have shown that the SCN is responsive to ethanol (Chen et al, 2004;Prosser and Glass, 2009;. Studies in different species have illustrated that circadian clock neurons are important for alcohol tolerance and that alcohol can modulate circadian phase-shifting (Brager et al, 2010;Ghezzi et al, 2013;McElroy et al, 2009;Prosser and Glass, 2009;Ruby et al, 2009;. In this study, animals consumed far less alcohol (and for a shorter period of time) than the study by Chen et al (2004), showing chronic ethanol liquid diet alters SCN rPer2 gene expression or the study by , showing chronic (no choice) ethanol consumption alters circadian activity rhythms; thus, we would not have expected changes in circadian gene expression in the SCN or altered circadian rhythms with this paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the most consistent effects have been seen under conditions of forced ethanol intake, presumably due to the higher levels of intake engendered under such conditions (Seggio et al, 2009). These observations could reflect the development of ethanol tolerance at the level of the suprachiasmatic circadian pacemaker (Lindsay, Glass, Amicarelli, & Prosser, 2014; Prosser & Glass, 2009). In the present study, all animals showed shortening of circadian period during the initial 15-day block of voluntary ethanol intake relative to water-only baseline conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, ethanol alters fundamental aspects of circadian pacemaker function (Brager, Ruby, Prosser, & Glass, 2010; Mistlberger & Nadeau, 1992; Rosenwasser, Fecteau, & Logan, 2005; Rosenwasser, Logan, & Fectau, 2005; Seggio, Fixaris, Reed, Logan, & Rosenwasser, 2009; Seggio, Logan, & Rosenwasser, 2007). Systemically administered ethanol reaches the suprachiasmatic nucleus (SCN), site of the “master” circadian pacemaker (Brager, Ruby, Prosser, & Glass, 2011; Ruby, Brager, DePaul, Prosser, & Glass, 2009; Ruby, Prosser, DePaul, Roberts, & Glass, 2009), and alters circadian function in part via effects on SCN neural signaling (McElroy, Zakaria, Glass, & Prosser, 2009; Prosser & Glass, 2009; Prosser, Mangrum, & Glass, 2008) and gene expression (Chen, Kuhn, Advis, & Sarkar, 2004; Madeira et al, 1997). Conversely, both environmental (Clark, Fixaris, Belanger, & Rosenwasser, 2007; Gauvin et al, 1997; Rosenwasser, Clark, Fixaris, Belanger, & Foster, 2010) and genetic (Brager, Prosser, & Glass, 2011; Ozburn et al, 2013; Spanagel et al, 2005) disruption of circadian function alters voluntary ethanol intake.…”
Section: Introductionmentioning
confidence: 99%
“…The SCN is responsive to ethanol in that acute ethanol can prevent photic resetting and chronic ethanol disrupts photic entrainment (4548). Additionally, studies have illustrated that the SCN develops rapid tolerance to the effects of EtOH (49, 50). …”
Section: Introductionmentioning
confidence: 99%